Visual Neurons in the Superior Colliculus Innervated by Islet2+ or Islet2− Retinal Ganglion Cells Display Distinct Tuning Properties - Kay, Rachel B.; Triplett, Jason W. (Frontiers in Neural Circuits, 2017)
Throughout the visual system, different subtypes of neurons are tuned to distinct aspects of the visual scene, establishing parallel circuits. Defining the mechanisms by which such tuning arises has been a long-standing challenge for neuroscience. To investigate this, we have focused on the retina’s projection to the superior colliculus (SC), where multiple visual neuron subtypes have been described. The SC receives inputs from a variety of retinal ganglion cell (RGC) subtypes; however, which RGCs drive the tuning of different SC neurons remains unclear. Here, we pursued a genetic approach that allowed us to determine the tuning properties of neurons innervated by molecularly defined subpopulations of RGCs. In homozygous Islet2-EphA3 knock-in (Isl2EA3/EA3) mice, Isl2+ and Isl2- RGCs project to non-overlapping sub-regions of the SC. Based on molecular and anatomic data, we show that significantly more Isl2- RGCs are direction-selective (DS) in comparison with Isl2+ RGCs. Targeted recordings of visual responses from each SC sub-region in Isl2EA3/EA3 mice revealed that Isl2- RGC-innervated neurons were significantly more DS than those innervated by Isl2+ RGCs. Axis-selective (AS) neurons were found in both sub-regions, though AS neurons innervated by Isl2+ RGCs were more tightly tuned. Despite this segregation, DS and AS neurons innervated by Isl2+ or Isl2- RGCs did not differ in their spatial summation or spatial frequency tuning. Further, we did not observe alterations in receptive field size or structure of SC neurons innervated by Isl2+ or Isl2- RGCs. Together, these data show that innervation by Isl2+ and Isl2- RGCs results in distinct tuning in the SC and set the stage for future studies investigating the mechanisms by which these circuits are built.